ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI ROYAL KUNINGAN HOTEL - Rivera Pantro Sukma; Ricky Talumantak; Ardhi Eka Septiawan (LPPM Universitas Asa Indonesia, 2017)
Purpose- This study aims to determine the effect of compensation and motivation on the performance of Royal Hotel employees Design/methologi/approach- The type of data in this study is primary or data derived from the respondent. Data collection can be through questionnaire instrument. Population in this research is employee of Royal Hotel operational with sample 100 responden and purposely (Purposive Sampling). The method of analysis using descriptive and quantitative methods. Findings-The result of research to partial variable, t value bigger than t table, hence show and indicate there is positive and significant influence between compensation and motivation to performance of Royal Hotel employee. While the percentage of influence on compensation and motivation given to Royal Hotel employees of 11.8% while the rest is influenced by other variables such as leadership, work environment and others.